Efforts to Improve Elementary School Students' Public Speaking Skills in Routine Friday Sermon Activities at UPT SDN 17 Pulau Punjung and SD IT Al-Bina 02 Pulau Punjung - Rizki, Babur; Hendra, Anton Nofri; M, Yopi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This classroom action research aims to improve the public speaking skills of elementary school students through a routine Friday sermon (kultum) activity at two schools: UPT SDN 17 Pulau Punjung and SD IT Al-Bina 02 Pulau Punjung. The problem underlying this research is the low level of confidence, fluency, articulation, and expression of students when delivering ideas orally in front of an audience. The research was conducted in two cycles, each consisting of the planning, action, observation, and reflection stages. The research subjects were 50 fifth-grade students from both schools. Data were collected through observation, interviews, field notes, and documentation. The results showed that the Friday sermon activity significantly improved students’ speaking skills, particularly in terms of confidence, intonation, articulation, expression, and fluency. In the first cycle, improvements began to appear although some students still lacked self-confidence. After improvements were made in the second cycle through routine practice, simulations, and giving appreciation, the students’ speaking skills improved optimally. Therefore, Friday sermons proved effective as a learning medium to build confidence and oral communication skills among elementary school students.